Negotiating Tradition and Digitalization: The Cultural Agency of Indigenous Communities in Social Media Adaptation in Indonesia - Paelani Setia; Moh. Dulkiah; Muhammad Ikhlas Rosele; Kristining Seva; Renatha Aisya Nazwanindya (Integritas Terbuka: Peace and Interfaith Studies, 2026)
This study analyzes how indigenous communities in Indonesia, particularly the Cireundeu Indigenous Community, manage the relationship between tradition and digitalization through practices of cultural agency in the use of social media. The study employs a qualitative approach with a case study design through interviews, participant observation, and analysis of community social media content. The findings show that digital adaptation in Cireundeu occurs through three forms of cultural agency. First, community elders demonstrate a cautious attitude toward social media as an effort to preserve the continuity of cultural values (resist). Second, the community adjusts the use of technology to existing customary norms (negotiate). Third, younger generations utilize social media for cultural education, tourism promotion, identity representation, and local economic development (enact). This process is supported by collaboration among community members, universities, local government institutions, and other digital actors. The study shows that the community does not perceive social media as a threat to tradition. Instead, community members use social media as a medium to reproduce cultural identity and expand the visibility of the indigenous community. This study contributes to the scholarship on indigenous communities and digital transformation by proposing a cultural agency-based digital adaptation model that explains the relationship between tradition and technology within the context of indigenous communities in Indonesia.